EXTRACURRICULAR ACTIVITIES – AN EFFECTIVE FORM OF LEARNING SUPPORT AT THE FACULTY OF POLITICAL EDUCATION, HANOI UNIVERSITY (Journal of Foreign Language Studies, 2022)
Extracurricular activities in universities have an increasingly important role in contributing to the overall achievement of education and training. In recent years, Hanoi University has regularly organized extracurricular activities for students associated the training contents. Typically, regarding modules of Political education, extracurricular activities are aimed at equipping students with vast and practical knowledge, promoting patriotism, and contributing to improving the quality of political, ideological and ethical education at the university. Besides, students are also provided with opportunities to improve their soft skills, group work skills and discipline, and to develop their independent thinking and cognitive ability.
Keywords: extracurricular; politics; learning support